2018
DOI: 10.1002/bit.26799
|View full text |Cite
|
Sign up to set email alerts
|

Direct conversion of cellulose into ethanol and ethyl‐β‐d‐glucoside via engineered Saccharomyces cerevisiae

Abstract: Simultaneous saccharification and fermentation (SSF) of cellulose via engineered Saccharomyces cerevisiae is a sustainable solution to valorize cellulose into fuels and chemicals. In this study, we demonstrate the feasibility of direct conversion of cellulose into ethanol and a biodegradable surfactant, ethyl-β-d-glucoside, via an engineered yeast strain (i.e., strain EJ2) expressing heterologous cellodextrin transporter (CDT-1) and intracellular β-glucosidase (GH1-1) originating from Neurospora crassa. We ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…Nevertheless, water activity should be regulated in a way that avoids secondary hydrolysis, which results in the reduction of yield, but sufficient to maintain enzyme activity for optimal reaction and allow substrate solubilization. In general, reverse hydrolysis is considered as a simpler and cost-efficient process if compared to transglycosylation. This is because the feedstock used in this process, i.e., glucose or any monosaccharide, is naturally available and considerably cheaper than a glycosyl donor (e.g., 4-nitrophenyl β- d -glycopyranoside, disaccharide) that is used in transglycosylation as in Figure . ,, Nevertheless, Jayakody et al have demonstrated that microcrystalline cellulose could be exploited as a substrate for the transglycosylation process, which reveals the potential of using natural cellulose. Similarly, Jocquel et al reported the use of wheat bran as a substrate with the presence of pentanol and enzyme cocktails and were able to transglycosylate xylan into pentyl β- d -xyloside with a different degree of polymerization, together with the byproduct’s xylose and glucose.…”
Section: Production Of S-apg Through Biological Routementioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, water activity should be regulated in a way that avoids secondary hydrolysis, which results in the reduction of yield, but sufficient to maintain enzyme activity for optimal reaction and allow substrate solubilization. In general, reverse hydrolysis is considered as a simpler and cost-efficient process if compared to transglycosylation. This is because the feedstock used in this process, i.e., glucose or any monosaccharide, is naturally available and considerably cheaper than a glycosyl donor (e.g., 4-nitrophenyl β- d -glycopyranoside, disaccharide) that is used in transglycosylation as in Figure . ,, Nevertheless, Jayakody et al have demonstrated that microcrystalline cellulose could be exploited as a substrate for the transglycosylation process, which reveals the potential of using natural cellulose. Similarly, Jocquel et al reported the use of wheat bran as a substrate with the presence of pentanol and enzyme cocktails and were able to transglycosylate xylan into pentyl β- d -xyloside with a different degree of polymerization, together with the byproduct’s xylose and glucose.…”
Section: Production Of S-apg Through Biological Routementioning
confidence: 99%
“…It allows enzymatic reactions to perform in a natural cellular environment, which protects the enzyme from degradation. In a study of Jayakody et al, 75 cellulose was fermented by Saccharomyces cerevisiae EJ2 with the supplementation of cellulase to coproduce bioethanol and ethyl β-Dglucoside. This strain produced β-glucosidase GH1-1 and cyclodextrin transporter CDT-1 intracellularly.…”
Section: Production Of S-apg Through Biological Routementioning
confidence: 99%
See 1 more Smart Citation
“…The small yields of ethanol obtained in fermentation (typically 10% (v/v)) currently need subsequent energy intensive distillation. Conventional ethanol plants will expend more than 30 per cent of bioethanol fuel's heat energy during the distillation process [49,85,86].…”
Section: Fermentation To Bioethanolmentioning
confidence: 99%
“…Although fuel ethanol has been the main product of interest in most of the studies discussed above, the formation of other biotechnological compounds has also been reported using the iCELL approach, e.g. 2,3-butanediol (Nan et al 2014), lactic acid (Turner et al 2016), and biosurfactants (Jayakody et al 2018).…”
Section: The Icell Componentmentioning
confidence: 99%